Aesthetic dance as woman's culture in America at the turn of the twentieth century: Genevieve Stebbins and the New York school of expression. Issue 3 (2nd September 2022) - Lynch, Kelly Jean
ABSTRACT: This essay provides a historical overview of "new" aesthetic dance practices in the United States between 1890 and 1920 before the advent of modern dance. At the turn of the twentieth century women were the main practitioners of the developing aesthetic dance genres known alternatively as gymnastic, expressive, natural, interpretive, or classic dancing. Aesthetic dance practices were informed by aesthetic theories of expression. One of the most prominent educational aesthetic methods amongst women was the Delsarte System of Expression. The leading advocate, educator, and innovator contributing to the development of this system was Genevieve Stebbins. This essay concludes with an exploration of her pedagogy as taught at the New York School of Expression and her performances in theaters and women's clubs.